2012
DOI: 10.1155/2012/308252
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targets for the Treatment of Juvenile Myelomonocytic Leukemia

Abstract: Significant advances in our understanding of the genetic defects and the pathogenesis of juvenile myelomonocytic leukemia (JMML) have been achieved in the last several years. The information gathered tremendously helps us in designing molecular targeted therapies for this otherwise fatal disease. Various approaches are being investigated to target defective pathways/molecules in this disease. However, effective therapy is still lacking. Development of specific target-based drugs for JMML remains a big challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…Identification of relevant target PTKs and a better understanding of the mechanisms of how mutant Cbl proteins promote oncogenesis represent exciting areas of ongoing and future research. Several recent reviews have summarized progress and emerging trends in this area [62,198201]. It is somewhat intriguing that mutations of the linker and RING finger domains have thus far not surfaced in solid tumors.…”
Section: Functional Roles Of Cbl-family Proteinsmentioning
confidence: 99%
“…Identification of relevant target PTKs and a better understanding of the mechanisms of how mutant Cbl proteins promote oncogenesis represent exciting areas of ongoing and future research. Several recent reviews have summarized progress and emerging trends in this area [62,198201]. It is somewhat intriguing that mutations of the linker and RING finger domains have thus far not surfaced in solid tumors.…”
Section: Functional Roles Of Cbl-family Proteinsmentioning
confidence: 99%
“…AML is further classified by French, American and British (FAB) into M0 to M7 subtypes [5]. Chronic myeloid leukemia (CML) is less common childhood leukemia, and rarely few cases of chronic Myelomonoctic leukemia (CMML) and juvenile chronic Myelomonocytic leukemia (JMML) were also reported in children [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous work has shown that the SH2 domains, the C-terminal tyrosyl phosphorylation sites, and the scaffolding adapter Gab2 (Mohi et al 2005), in addition to tyrosyl phosphatase activity (Mohi et al 2005;Schubbert et al 2005), are required for mutant PTPN11-induced myeloproliferation, at least in mice, and as discussed above, it is hard to see how any of these domains/intermediates would be required for SHP2-mediated RUNX1 dephosphorylation. Furthermore, several other mutations that cause JMML KRAS and NRAS gain-of-function alleles or homozygous NF1 loss of function (Schubbert et al 2007;Liu et al 2012) are believed to lie downstream from SHP2 in receptor tyrosine kinase and cytokine signaling, and it is unclear how/whether they too would converge to dephosphorylate RUNX1. Nevertheless, the unexpected nexus between SFKs, RUNX1, and SHP2 represents an arena for future investigations into normal and abnormal hematopoiesis.…”
Section: Fmentioning
confidence: 99%